The Role of Digital Marketing Management in Improving College Branding on Social Media - Nurul Rezki Awaliah S; Ummu Muhaeminah; Izzatul Munawwaroh (Indonesian Journal of Progressive Pedagogy, 2025)
This study analyzes the role of digital marketing management in enhancing higher education branding through social media. The focus is to explore best practices, challenges, and opportunities faced by higher education institutions in the digital era. Social media has proven to be a strategic tool to reach a wider audience, build institutional image, and increase interaction with prospective students. However, challenges such as limited human resource competency and competition between higher education institutions remain significant barriers. This study recommends an innovative approach in digital marketing strategy to support the transformation of higher education in Indonesia. With an integrated and adaptive approach, higher education institutions can maintain relevance, increase brand awareness, and build long-term relationships with audiences.